2017
DOI: 10.1007/s00125-017-4330-3
|View full text |Cite
|
Sign up to set email alerts
|

The GLP-1 analogue lixisenatide decreases atherosclerosis in insulin-resistant mice by modulating macrophage phenotype

Abstract: Lixisenatide decreases atheroma plaque size and instability in Apoe Irs2 mice by reprogramming macrophages towards an M2 phenotype, which leads to reduced inflammation. This study identifies a critical role for this drug in macrophage polarisation inside plaques and provides experimental evidence supporting a novel mechanism of action for GLP-1 analogues in the reduction of cardiovascular risk associated with insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 40 publications
1
54
0
3
Order By: Relevance
“…In our study ApoE −/− mice received a single daily dose of 300 μg/kg liraglutide for 6 weeks resulting in significant reduction of lesion progression at the iliac bifurcation of the aorta. Previous in vivo studies administered liraglutide for 4 weeks [ 30 32 , 35 ]. 300 μg/kg liraglutide has previously shown to have little effect on weight loss [ 24 , 36 ] meaning the atheroprotective effects we report are weight-independent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study ApoE −/− mice received a single daily dose of 300 μg/kg liraglutide for 6 weeks resulting in significant reduction of lesion progression at the iliac bifurcation of the aorta. Previous in vivo studies administered liraglutide for 4 weeks [ 30 32 , 35 ]. 300 μg/kg liraglutide has previously shown to have little effect on weight loss [ 24 , 36 ] meaning the atheroprotective effects we report are weight-independent.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have addressed the effect of liraglutide on the inflammatory status of monocytes and macrophages in vivo in the context of atherosclerosis. Most recently Vinué et al reported that lixisenatide decreases atherosclerosis in insulin resistant mice by reprogramming macrophages towards an MΦ2 phenotype [ 35 ]. Indeed, our initial approach using THP-1 monocytes suggested that liraglutide influences monocyte/macrophage cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that signalling through the GLP‐1 receptor has direct effects to inhibit the formation and promote the stability of atheromatous plaques. In experimental models, GLP‐1 receptor agonists reduce the infiltration of macrophages, promote thicker fibrous caps and minimize smooth muscle proliferation . The net effect of these actions is a slowing of the atherosclerotic process, an attenuation of the inflammatory response in blood vessels, and a reduction in the likelihood of plaque rupture.…”
Section: Interplay Of Glucagon‐like Peptide‐1 Signalling and Neprilysmentioning
confidence: 99%
“…In addition, signalling through the GLP-1 receptor may have direct effects of inhibiting atheroma formation and promoting plaque stability [24,25], which may underlie the ability of long-acting receptor agonists to reduce the occurrence of thromboembolic events ( Fig. 1) [11][12][13].…”
Section: Contrasting Macrovascular Effects Of Natriuretic Anti-hypergmentioning
confidence: 99%